Study on filter clogging and filtration performance evaluation of Ballast Water Management System (BWMS) using analytical and numerical methods - Gang Nam Lee; Tien Trung Duong; Sangho Park; Mansoo Kim; Kwang Hyo Jung (Brodogradnja)
Filter clogging is a critical issue in ballast-water management systems (BWMSs) and is caused by the accumulation of sediment deposits and particles in water, particularly under high total suspended solid (TSS) conditions. Despite its significance, studies focusing on the prediction and prevention of clogging, as well as detailed investigations into its mechanisms, remain limited. In this study, an analytical method based on Darcy’s law is devised to predict clogging occurrences and filter performance is evaluated via computational fluid dynamics (CFD) simulations. Additionally, a coupled CFD-discrete element method (DEM) approach is employed to investigate clogging mechanisms at the microscopic level, thus providing detailed insights into particle behaviour and fluid dynamics. The results show that clogging occurred rapidly under high-TSS conditions and that the estimated clogging time closely matched the analytical predictions and CFD simulations. Results of CFD-DEM simulation show that larger particles initially obstructed screen pores, followed by a rapid surface coverage, which ultimately increased the pressure drop significantly. The proposed methods offer a reliable framework for evaluating BWMS filter performance and provide foundational data for the development of next-generation filters capable of preventing clogging in high-turbidity environments.